ANALISIS EKSPEKTASI INFLASI DI SUMATERA UTARA - Ariwan Rezeki; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2013)
Inflation is an indicator to see the rate of change, and is considered to occur if the price increase takes place continuously and mutually-affecting effect. The level of inflation is determined by forces of demand and supply for goods and services that reflect the behavior of market participants or the public. One of the factors that influence people's behavior is the expectation of the inflation rate in the future. Expectations of high inflation that will encourage people to divert its financial assets into real assets, such as land, houses, and other consumer goods. Vice versa expectations of low inflation rates will provide incentives for people to save and invest in productive sectors. Public expectations for inflation in the future, among others, can be seen from the development of the nominal interest rate. The nominal interest rate reflects the real interest rate plus expected inflation. Thus, the development of the nominal interest rate can be used as an indicator of the public's expectations.This analysis using regression and cointegration to examine the relationship of short-term and long-term inflation spreads between the interest rate spread. From the results obtained for the short-term and long-term spreads are able to explain in a period equal to the period of significant inflation expectations and the direction of movement in both the short and long-term inflation expectations deposit interest rate spread is only 3 and 12 months. However, the model still can not be used to make projections of inflation expectations.Keywords : inflation, interest rates, expectations, cointegration,regression.